2006
DOI: 10.1080/00036840500215303
|View full text |Cite
|
Sign up to set email alerts
|

Education and skills mismatch in the Italian graduate labour market

Abstract: Abstract:This paper focuses on education and skills mismatch amongst Italian graduates.Indicators for over and under-utilisation of education and under-utilisation of skills are included in a grouped data lognormal wage equation, allowing us to test a number of theories which could explain the effect of over-schooling on wages. We find little evidence to support assignment theory and also identify a relatively weak wage effect arising from educational mismatch associated with the formal requirements of a job, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 31 publications
4
91
1
4
Order By: Relevance
“…The final mark at graduation does not affect wages. This finding is not in line with Di Pietro and Urwin (2006) who, in studying a sample of Italian graduates in 1998, three years after graduation, find that those graduates who obtained a poor mark (between 70 and 89.99) at university earned approximately 3% less than their peers whose mark was between 105 and 110. By studying a random sample of economics graduates from the 'Parthenope' University of Naples, Quintano et al (2008) obtain similar results: graduates with a high mark at graduation (105/110 and more) are more likely to earn a high wage.…”
Section: Research In Applied Economicscontrasting
confidence: 61%
See 1 more Smart Citation
“…The final mark at graduation does not affect wages. This finding is not in line with Di Pietro and Urwin (2006) who, in studying a sample of Italian graduates in 1998, three years after graduation, find that those graduates who obtained a poor mark (between 70 and 89.99) at university earned approximately 3% less than their peers whose mark was between 105 and 110. By studying a random sample of economics graduates from the 'Parthenope' University of Naples, Quintano et al (2008) obtain similar results: graduates with a high mark at graduation (105/110 and more) are more likely to earn a high wage.…”
Section: Research In Applied Economicscontrasting
confidence: 61%
“…However, in Southern Italy, an area with high unemployment and a relatively high percentage of graduates, the hidden over-education phenomenon could well be quite marked. In fact, the possibility exists that employers are attempting to benefit from the increased supply of graduates by re-categorizing jobs as positions requiring a degree, when neither the education required nor the wage scale associated with the job are graduate level (Note 6) (Di Pietro and Urwin, 2006). …”
Section: Research In Applied Economicsmentioning
confidence: 99%
“…Following the specification developed by Verdugo and Verdugo (1989), different studies have included dummy variables for both educational and skill mismatch in the empirical analysis (Allen and van der Velden, 2001;Di Pietro and Urwin, 2006;Green and McIntosh, 2007;Sánchez-Sánchez and McGuiness, 2013;Mavromaras et al 2013). It has been found that overeducation and overskilling have both a negative and statistically significant effect on earnings within the same level of education, the overeducation effect being much higher than the overskilling effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While various studies propose that the developments in higher education have resulted in an over-supply of college graduates (e.g. Di Pietro and Urwin 2006;Hartog 2000;Mason 1996), ample evidence points out that the supply of highskilled workers failed to keep pace with the demand for skilled labour (Bound and Johnson 1992;Katz and Murphy 1992). Conclusions on the labour market implications of the expansion in tertiary education therefore remain inconclusive and mostly limited to the perspective of employees (see e.g.…”
Section: Introductionmentioning
confidence: 99%